Hubungan Kejadian Hipertensi dengan Fungsi Kognitif pada Lansia di Desa Jampiroso Selatan Kota Temanggung - Finishi Zarrahida Alislami; suwanti suwanti (Universitas Ngudi Waluyo, 2021)
Hypertension is a factor in the decline in cognitive function. One of the complications of hypertension in the central nervous system besides stroke can also cause decreased cognitive function (Vascular Cognitive Impairment). The problem of elderly with hypertension is the biggest factor affecting the decline in cognitive function. This study to determine the relationship between incidence of hypertension and cognitive function in the elderly in Jampiroso Selatan Village, Temanggung City. This study used descriptive correlation design with cross-sectional approach. The population of this study was 118 people. The sampling method was used proportionate stratified random sampling with a total of 60 respondents. The research instrument used MMSE (Mini Mental Status Examination) questionnaire. Analyze data was used Spearman-Rank test.This study showed that the elderly who had hypertension were in stage II hypertension as much as 42 (70.0%), normal elderly cognitive function was 33 (76.7%) and probable cognitive impairment was 9 (52.9%).The results of statistical test using the Spearman-Rank showed p-value = 0.012 (<0.05), which means that there was a relationship between the incidence of hypertension and cognitive function in the elderly. To avoid cognitive function problem, elderly with hypertension can control their blood pressure regularly by participating in Integrated Healthcare Centre and adopting a healthy lifestyle. Key words: cognitive function, elderly, incidence of hypertension